Finite element analysis of catastrophic failure of dynamically-loaded countersunk composite fuselage joints. (1st December 2015) - Egan, B.; McCarthy, M.A.; Frizzell, R.M.; McCarthy, C.T.
Abstract: Accurate models of dynamic structural failure are important for crashworthiness studies. To date, catastrophic failure of dynamically-loaded composite bolted joints has been studied using global or stacked shell element models. In this paper, high-fidelity (three-dimensional solid) explicit FE models are used to simulate catastrophic failure of countersunk composite fuselage joints. While current state-of-the-art 3D modelling approaches focus almost exclusively on the prediction of composite damage, this study also investigates the treatment of fastener damage. Fastener fracture is a common catastrophic joint failure mode, particularly in joints designed to initially fail in bearing. A Johnson–Cook material model and cohesive elements were used to predict plasticity, damage and fracture of the titanium (Ti–6Al–4V) fastener. Although a model calibration was required, due to the complex interaction of model parameters, numerical results demonstrate key trends of experiments and provide a starting point for the development of more predictive approaches for simulating fastener failure.